Pilot assessment of a virtual intensive outpatient program for adults with eating disorders. (26th August 2020) - Blalock, Dan V.; Le Grange, Daniel; Johnson, Craig; Duffy, Alan; Manwaring, Jamie; Tallent, Casey N.; Schneller, Karen; Solomon, Ashley M.; Mehler, Philip S.; McClanahan, Susan F.; Rienecke, Renee D.
Abstract: Access to evidence‐based treatment for eating disorders is severely limited by patient barriers and available clinician training. While clinical parameters often point to the need for a high level of care, patients may resist pursuing higher levels of care due to these barriers. One option that might mitigate such obstacles is the provision of a higher level of care via internet‐based treatment for eating disorders. We sought to determine the feasibility, acceptability, and preliminary clinical outcomes associated with treatment of eating disorders through virtual intensive outpatient programming (VIOP). Fifty‐seven patients meeting DSM‐5 criteria for an eating disorder participated in VIOP. Of the 57 patients in VIOP treatment, 3 did not complete voluntary measures at admission or discharge, and 9 additional patients did not complete voluntary measures at discharge. Overall, 45 VIOP patients completed admission and discharge assessments, including a net promoter score (NPS) question assessing patient acceptability. Recruitment, treatment adherence, and completion of assessments in VIOP were feasible and acceptable. VIOP patients showed significant and clinically meaningful improvements in all outcomes measured, including self‐reported eating disorder symptoms, depression, self‐esteem, quality of life, and overall satisfaction. VIOP appears feasible, acceptable, and evidences clinically meaningful changes in eating and mood disorder symptoms.